Development and validation of a real‐time multiplex PCR assay for the detection of dermatophytes andFusariumspp. Issue 11 (November 2019) - Koo, Seok Hwee; Teoh, Yee Leng; Koh, Wei Liang; Ochi, Harumi; Tan, Sher Kye; Sim, Diana Miao Fang; Jiang, Boran; Tan, Ai Ling; Tan, Thean Yen; Lim, Su Ping Regina
Abstract : Introduction: : Onychomycosis is a debilitating, difficult‐to‐treat nail fungal infection with increasing prevalence worldwide. The main etiological agents are dermatophytes, which are common causative pathogens in superficial fungal mycoses. Conventional detection methods such as fungal culture have low sensitivity and specificity and are time‐consuming. Aim: : The main objective of this study was to design, develop and validate a real‐time probe‐based multiplex qPCR assay for the detection of dermatophytes and Fusarium species. Methodology: : The performance characteristics of the qPCR assays were evaluated. The multiplex qPCR assays targeted four genes (assay 1: pan‐dermatophytes /Fusarium spp.; assay 2: Trichophyton rubrum/Microsporum spp.). Analytical validation was accomplished using 150 fungal isolates and clinical validation was done on 204 nail specimens. The performance parameters were compared against the gold standard (fungal culture) and expanded gold standard (culture in conjunction with sequencing). Results: : Both the single‐plex and multiplex qPCR assays performed well especially when compared against the expanded gold standard. Among the 204 tested nail specimens, the culture method showed that 125 (61.3 %) were infected with at least one organism, of which 40 yielded positive results for dermatophytes and Fusarium spp. These target organisms detected include 20 dermatophytes and 22 Fusarium spp. The developed qPCR assays demonstrated excellent limit of detection, efficiency, coefficient of determination, analytical and clinical sensitivity and specificity. Conclusion: : The multiplex qPCR assays were reliable for the diagnosis of onychomycosis, with shorter turn‐around time as compared to culture method. This aids in the planning of treatment strategies to achieve optimal therapeutic outcome.